Coating induced residual stress in nonoriented electrical steel laminations. Issue 16 (2nd September 2014) - Ding, Yaoyao; Gallaugher, Matthew; Brodusch, Nicolas; Gauvin, Raynald; Chromik, Richard R.
Abstract